2014
DOI: 10.1186/1744-8069-10-23
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupuncture Needle Combination on Central Pain Processing-An fMRI Study

Abstract: BackgroundEmpirical acupuncture treatment paradigm for acute pain utilizing Tendinomuscular Meridians (TMM) calls for the stimulation of Ting Points (TPs) and Gathering point(GP). This study aims to compare the supraspinal neuronal mechanisms associated with both TPs and GP needling (EA3), and TPs needling alone (EA2) with fMRI.ResultsA significant (P < 0.01) difference between pre-scan (heat Pain) HP, and post-EA HP VAS scores in both paradigms was noted (n = 11). The post-EA HP VAS score was significantly (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Interestingly, in the present study, the brain region, demonstrating a decreased DC after acupuncture at the ipsilateral acupoint, was in the cerebellum bilaterally overlapped with the vermal lobules IV/V. Similarly, Leung et al demonstrated that changes in pain perception after acupuncture are associated with reduced functional activity in the cerebellum [45]. Our findings extended these observations obtained from measuring regional activity by calculating the full range of functional connectivity of the cerebellum to the whole brain, thereby illustrating a hublike role of the cerebellum in pain relief using ipsilateral acupuncture for the first time.…”
supporting
confidence: 68%
“…Interestingly, in the present study, the brain region, demonstrating a decreased DC after acupuncture at the ipsilateral acupoint, was in the cerebellum bilaterally overlapped with the vermal lobules IV/V. Similarly, Leung et al demonstrated that changes in pain perception after acupuncture are associated with reduced functional activity in the cerebellum [45]. Our findings extended these observations obtained from measuring regional activity by calculating the full range of functional connectivity of the cerebellum to the whole brain, thereby illustrating a hublike role of the cerebellum in pain relief using ipsilateral acupuncture for the first time.…”
supporting
confidence: 68%
“…33 Cerebellar structure and function are also integral to models that detect and predict experimental pain 79 and clinical pain, 78 and changes in pain perception after acupuncture have been associated with reduced functional activity in the posterior cerebellum. 38 Other evidence shows that transcranial direct current stimulation over the cerebellum influences the perception of both pain-eliciting and non-pain-eliciting stimuli, with current flow models suggesting that these effects are driven by focal stimulation over lobules VI and VIIb. 9 In our study, activity in posterior cerebellum was found during separate trials of pain and force production, when pain processing and force production were combined and also when the FP and FW conditions were directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…Brain imaging studies have also shown that acupuncture needle stimulation1718192021 can evoke widespread brain activity changes and modulate the functional connectivity (FC) of the pain processing network2223242526272829, which opens a new window to understand the central mechanism of acupuncture treatment.…”
mentioning
confidence: 99%